ADAPTATION PERIOD OF PUPILS: SOCIO-PEDAGOGICAL ASPECT - Ukstina, Rita (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Analyzing the causes of academic failure of the first class pupils, the child's inability to get involved in the mainstream class is often mentioned as one of them which comes along with low self-esteem and mistrust in his/her intellectual abilities. Therefore in recent years, one of the research fields of social pedagogues is child's adaptation in the first class. This study analyzes the knowledge of various authors on factors that determine the psychological and social adaptation of the child in socio-pedagogical perspective. Theoretical aspects of adaptation are explored in order to determine the causes which hinder successful adaptation, and socio-pedagogical theories are analyzed elaborating support models for the whole class, teachers, parents and individual children.